Review: Mesoporous Silica Formulation in Biopharmaceutical Classification System (BCS) Class II Drug Development - Ayodduki, Zahra Noor Silmi Hermawan; Anggi, Joseph Fide; Nurulaini, Siti Nunung; Budiman, Arif; Aulifa, Diah Lia (Indonesian Journal of Pharmaceutics, 2025)
About 40% of approved drugs and nearly 90% of drug candidates have low aqueous solubility which limits their bioavailability resulting in suboptimal pharmacological activity. According to the Biopharmaceutical Classification System (BCS), drugs with low solubility and high permeability are categorized as BCS Class II, where the dissolution rate becomes a key factor in gastrointestinal absorption. One approach to increasing its solubility is the formation of an amorphous state, which lowers lattice energy and enhances dissolution. However, the amorphous form tends to be unstable and prone to recrystallization. Mesoporous silica has been developed as a drug delivery system capable of maintaining the stability of the amorphous form through molecular interactions with silanol groups and the nano-confinement effect that suppresses crystal growth. With a high surface area and tunable pore structure, mesoporous silica enhances the dissolution rate and bioavailability of BCS Class II drugs, ultimately contributing to improved pharmacological activity. This review summarizes the development of mesoporous silica formulations in drug delivery systems for BCS Class II drugs to enhance their pharmacological efficacy.